A method for preparing high entropy boride coating

Through the spraying technology of high-entropy boricide microspheres, the problem of poor density of high-entropy boric coatings is solved, and the density and oxidation resistance of high-entropy boric coatings are improved, ensuring effective protection of the matrix.

CN116693298BActive Publication Date: 2024-12-20BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310735655.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2024-12-20
Estimated Expiration
2043-06-20

AI Technical Summary

Technical Problem

The existing high entropy boric coatings have poor density and are difficult to maintain antioxidant properties at high temperatures, which affects the protective effect of the matrix.

Method used

Spray granulation is carried out by mixing high entropy boricide, dispersant and binder. After the first sintering and second sintering, high entropy boric microspheres are formed, and sprayed on the substrate with them as coating, and enhanced by melting. The bond between particles improves the density of the coating.

Benefits of technology

The denseness and cohesion strength of the high-entropy boride coating are improved, the binding force with the matrix is ​​enhanced, and the phase stability and oxidation resistance of the high-entropy boride are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116693298B_ABST
    Figure CN116693298B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of high entropy borides, and specifically relates to a method for preparing a high entropy boride coating. The present invention provides a method for preparing a high entropy boride coating, comprising the following steps: mixing a high entropy boride, a dispersant and a binder, spraying and granulating the obtained slurry to obtain a spherical material; sequentially performing a first sintering and a second sintering on the spherical material to obtain high entropy boride microspheres; using the high entropy boride microspheres as a coating, spraying on a substrate to obtain the high entropy boride coating. The high entropy boride coating obtained by the present invention has high density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high entropy borides, and in particular relates to a method for preparing a high entropy boride coating. Background Art

[0002] Diboride is used as a coating material to protect lightweight fiber-reinforced composite materials from oxidation because of its high thermal conductivity, high elastic modulus and high hardness. Due to its poor sintering properties, sintering aids are often added to it to help densification, but at the same time, it will cause the oxidation resistance to decrease at high temperatures, making it difficult to effectively protect the matrix.

[0003] High entropy ceramics are a new type of ceramics with multiple components (five or more components) dissolved in a single-phase solid solution, which has a high entropy value. Among them, the research on high entropy ceramic materials mainly focuses on high entropy oxides, high entropy borides and high entropy carbides. High entropy borides have attracted much attention due to their comprehensive characteristics such as high melting point, excellent mechanical properties and high thermal stability. Among them, high entropy borides show better antioxidant properties, which provides the possibility for high entropy borides to be used as antioxidant ablation coatings.

[0004] At present, the methods for preparing high entropy borides include: high energy ball milling combined with heat treatment, high energy ball milling combined with spark plasma sintering, or magnetron sputtering, etc. However, the coatings prepared from the high entropy borides obtained by the above methods still have the defect of poor density. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a high entropy boride coating. The high entropy boride coating obtained by the method provided by the present invention has higher density.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a high entropy boride coating, comprising the following steps:

[0008] The high entropy boride, dispersant and binder are mixed, and the obtained slurry is spray granulated to obtain a spherical material;

[0009] The spherical material is subjected to a first sintering and a second sintering in sequence to obtain high entropy boride microspheres;

[0010] The high entropy boride microspheres are used as coating and sprayed on a substrate to obtain the high entropy boride coating.

[0011] Preferably, the metal elements in the high entropy boride include at least five of Hf, Zr, Nb, Ta, Sc, Ti, Lu, Tm, Er, Ho and Dy;

[0012] The molar amounts of the metal elements in the high entropy borides are the same;

[0013] The molar ratio of the total molar amount of the metal elements to the boron element is 1:2.

[0014] Preferably, the dispersant includes deionized water; and the binder includes polyvinyl alcohol.

[0015] Preferably, the solid content of the slurry is 40wt%;

[0016] The mass of the binder is 0.4 wt % of the mass of the high entropy boride.

[0017] Preferably, the mixing method is ball milling; the grinding balls used in the ball milling include first grinding balls, second grinding balls and third grinding balls;

[0018] The diameter of the first grinding ball is 10 mm, the diameter of the second grinding ball is 5 mm, and the diameter of the third grinding ball is 2 mm;

[0019] The mass ratio of the first grinding ball, the second grinding ball and the third grinding ball is 1.8-2.2:1.8-2.2:1;

[0020] The ball-to-material ratio of the ball milling mixture is 4:0.8-1.2;

[0021] The ball milling mixing has a rotation speed of 200 to 400 rpm and a time of 2 to 4 hours.

[0022] Preferably, the conditions for the spray granulation include: an inlet temperature of 240-280° C., an outlet temperature of 140-160° C., a peristaltic pump speed of 30-50 r / min, and a nozzle speed of 30-50 r / s.

[0023] Preferably, the first sintering temperature is 500-600°C, and the holding time is 2.8-3.2h;

[0024] The heating rate of heating to the first sintering temperature is 1-3°C / min.

[0025] Preferably, the second sintering temperature is 1400-1800°C, and the holding time is 1.8-2.2h;

[0026] The heating rate of heating to the second sintering temperature is 3-7° C. / min.

[0027] Preferably, the spraying is plasma spraying.

[0028] Preferably, the thickness of the high entropy boride coating is 100-400 μm.

[0029] The present invention provides a method for preparing a high entropy boride coating, comprising the following steps: mixing a high entropy boride, a dispersant and a binder, spraying and granulating the obtained slurry to obtain a spherical material; sequentially performing a first sintering and a second sintering on the spherical material to obtain a high entropy boride microsphere; using the high entropy boride microsphere as a coating, spraying on a substrate to obtain the high entropy boride coating. In the present invention, the binder can be volatilized by the first sintering, so that the material maintains a spherical shape, and further by the second sintering, the particles are melted, the cohesive strength is improved while retaining the sphericity, the fluidity of the obtained high entropy boride microsphere is improved, and then the density of the coating obtained by using the high entropy boride microsphere as a coating is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is the XRD pattern of the high entropy boride microspheres obtained in Example 1;

[0031] Figure 2 This is a SEM image of the high entropy boride microspheres obtained in Example 1, wherein Figure 2 a is a SEM image with a magnification of 400 times. Figure 2 b is a SEM image with a magnification of 1500 times;

[0032] Figure 3 is the XRD pattern of the high entropy boride coating obtained in Example 1;

[0033] Figure 4 is a SEM image of the high entropy boride coating obtained in Example 1, wherein Figure 4 c is the SEM image of the coating surface. Figure 4 d is the SEM image of the coating cross section. DETAILED DESCRIPTION

[0034] The present invention provides a method for preparing a high entropy boride coating, comprising the following steps:

[0035] The high entropy boride, dispersant and binder are mixed, and the obtained slurry is spray granulated to obtain a spherical material;

[0036] The spherical material is subjected to a first sintering and a second sintering in sequence to obtain high entropy boride microspheres;

[0037] The high entropy boride microspheres are used as coating and sprayed on a substrate to obtain the high entropy boride coating.

[0038] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0039] The invention mixes high entropy boride, dispersant and binder, and sprays and granulates the obtained slurry to obtain spherical material.

[0040] In the present invention, the metal elements in the high entropy boride preferably include at least five of Hf, Zr, Nb, Ta, Sc, Ti, Lu, Tm, Er, Ho and Dy. In the present invention, the molar amounts of the metal elements in the high entropy boride are preferably the same; the molar ratio of the total molar amount of the metal elements to the boron element is preferably 1:2.

[0041] In the present invention, the high entropy boride is preferably obtained by preparation, and the preparation method preferably comprises the following steps:

[0042] According to the composition of the high entropy boride, the corresponding metal oxide and boron carbide are mixed and vacuum sintered to obtain the high entropy boride.

[0043] In the present invention, the mixing process is preferably wet ball milling; the grinding balls of the wet ball milling are preferably zirconia grinding balls with a diameter of 10 mm, zirconia grinding balls with a diameter of 8 mm, zirconia grinding balls with a diameter of 5 mm and zirconia grinding balls with a diameter of 2 mm in a mass ratio of 1:2:3:4; the dispersion medium of the wet ball milling is preferably anhydrous ethanol.

[0044] In the present invention, the mass ratio of the total mass of the metal oxide and boron carbide, the dispersion medium and the grinding balls is preferably 1:2:4. In the present invention, the rotation speed of the wet ball milling is 300-350 rpm, more preferably 310-340 rpm, more preferably 320-330 rpm; the time is preferably 3-5 hours, more preferably 3-4 hours. In the present invention, the wet ball milling is preferably carried out in a planetary ball mill.

[0045] After the wet ball milling, the present invention also preferably includes sequentially performing rotary evaporation and drying on the obtained slurry; the temperature of the rotary evaporation is 70°C, the rotation speed is 35 rpm, and the time of the rotary evaporation is not particularly limited and can be adopted as known to those skilled in the art; the drying condition is drying at 100°C for 12 hours.

[0046] In the present invention, the temperature of the vacuum sintering is preferably 1600-1850°C, more preferably 1650-1800°C, and more preferably 1700-1750°C; the holding time is preferably 2-3.5h, and more preferably 2.5-3h. In the present invention, it is preferred to use a gradient heating method to heat up to the vacuum sintering temperature; the gradient heating preferably includes: heating to 900-1100°C at a heating rate of 8-12°C / min, and then heating to the vacuum sintering temperature at a heating rate of 3-7°C / min, and more preferably heating to 1000°C at a heating rate of 9-10°C / min, and then heating to the vacuum sintering temperature at a heating rate of 4-5°C / min. In the present invention, the process of gradient heating is adopted. When the temperature is low, a faster heating rate can speed up the heating rate and reduce the heating time; when the temperature is high and gradually approaches the reaction temperature, a slower heating rate can ensure that the powder is evenly heated, fully heated, and fully reacted.

[0047] In the present invention, the vacuum sintering is preferably carried out in a graphite vacuum sintering furnace. In a specific embodiment of the present invention, the process of the vacuum sintering is preferably: laying graphite paper in a graphite crucible, placing the obtained mixture on the graphite paper, and placing the graphite crucible in a graphite vacuum sintering furnace for vacuum sintering.

[0048] After the vacuum sintering, the present invention preferably further includes sequentially cooling, crushing, screening, solid-liquid separation and drying the obtained material.

[0049] In the present invention, the cooling process is preferably furnace cooling to room temperature.

[0050] In the present invention, the crushing process preferably includes: mixing the material, dispersion medium and grinding balls, and performing ball milling.

[0051] In the present invention, the dispersion medium preferably includes ethanol or water; the water is preferably deionized water, and the ethanol is preferably anhydrous ethanol. In the present invention, the mass ratio of the material to the dispersion medium is 1:1.8-2.2, and more preferably 1:2.

[0052] In the present invention, the grinding balls are preferably zirconia balls with a diameter of 10 mm, zirconia balls with a diameter of 8 mm, zirconia balls with a diameter of 5 mm and zirconia balls with a diameter of 2 mm, with a mass ratio of 0.8 to 1.2: 1.8 to 2.2: 2.8 to 3.2: 4, and the mass ratio is further preferably 1: 2: 3: 4. In the present invention, the mass ratio of the material, the dispersion medium and the grinding balls is preferably 1: 2: 4. In the present invention, the rotation speed of the ball mill is preferably 300 to 500 rpm, and more preferably 300 to 400 rpm; the time is preferably 4 to 6 hours, and more preferably 4 to 5 hours. In the present invention, the ball milling is preferably carried out in a planetary ball mill.

[0053] In the present invention, the sieve aperture used in the screening process is preferably 625 mesh.

[0054] In the present invention, the solid-liquid separation method is preferably rotary evaporation or filtration, and more preferably rotary evaporation. In the present invention, the temperature of the rotary evaporation is preferably 60-90°C, and more preferably 70-80°C; the rotary evaporation speed is preferably 30-50rpm, and more preferably 35-45rpm. The present invention does not have any special limitation on the time of the rotary evaporation, and the method well known to those skilled in the art can be adopted. The present invention does not have any special limitation on the filtering process, and the method well known to those skilled in the art can be adopted.

[0055] In the present invention, the drying temperature is preferably 80 to 120° C., more preferably 100 to 110° C.; the drying time is preferably 6 to 12 hours, more preferably 8 to 10 hours.

[0056] In the present invention, the dispersant preferably includes deionized water; the binder preferably includes polyvinyl alcohol; the solid content of the slurry is preferably 40wt%; and the mass of the binder is preferably 0.4wt% of the mass of the high entropy boride.

[0057] In the present invention, the mixing method of the high entropy boride, dispersant and binder is preferably ball milling; the grinding balls used in the ball milling mixing preferably include first grinding balls, second grinding balls and third grinding balls; the first grinding balls, the second grinding balls and the third grinding balls are preferably zirconia balls; the diameter of the first grinding balls is preferably 10 mm, the diameter of the second grinding balls is preferably 5 mm, and the diameter of the third grinding balls is preferably 2 mm; the mass ratio of the first grinding balls, the second grinding balls and the third grinding balls is preferably 1.8-2.2:1.8-2.2:1, and further preferably 2:2:1.

[0058] In the present invention, the ball-to-material ratio of the ball milling is preferably 4:0.8-1.2, more preferably 4:1. In the present invention, the rotation speed of the ball milling is preferably 200-400 rpm, more preferably 250-350 rrpm; the time is 2-4 hours, more preferably 2-3 hours.

[0059] In the present invention, the conditions for the spray granulation preferably include: an inlet temperature of 240-280°C, an outlet temperature of 140-160°C, a peristaltic pump speed of 30-50 r / min, and a nozzle speed of 30-50 r / s, and more preferably an inlet temperature of 250-270°C, an outlet temperature of 150-155°C, a peristaltic pump speed of 40-45 r / min, and a nozzle speed of 25-40 r / s. In the present invention, the peristaltic pump speed is the feed speed.

[0060] After obtaining the spherical material, the present invention sequentially performs a first sintering and a second sintering on the spherical material to obtain high entropy boride microspheres.

[0061] In the present invention, the first sintering temperature is preferably 500-600°C, more preferably 530-550°C; the heating rate to the first sintering temperature is preferably 1-3°C / min, more preferably 2°C / min; the holding time is preferably 2.8-3.2h, more preferably 3h.

[0062] In the present invention, the second sintering temperature is preferably 1400-1800°C, more preferably 1500-1700°C; the heating rate to the second sintering temperature is preferably 3-7°C / min, more preferably 5-6°C / min; the holding time is 1.8-2.2h, more preferably 2h.

[0063] In the present invention, the first sintering and the second sintering are preferably performed under normal pressure and vacuum conditions. In the present invention, the binder can be removed by the first sintering and the second sintering, and the spherical particles can be better combined together by sintering.

[0064] After the second sintering, the present invention also preferably includes cooling and sieving the obtained material. In the present invention, the cooling rate is preferably 4.8-5.2°C / min, more preferably 5°C / min; the temperature after cooling is preferably 30-50°C, more preferably 35-45°C. In the present invention, the cooling method is preferably furnace cooling.

[0065] In the present invention, the mesh size used in the sieving treatment is preferably 10 to 100 μm, more preferably 45 to 90 μm.

[0066] After obtaining the high entropy boride microspheres, the present invention uses the high entropy boride microspheres as a coating and sprays them on a substrate to obtain the high entropy boride coating.

[0067] In the present invention, the matrix preferably includes a C / C matrix, a C / SiC matrix or a high-temperature alloy matrix, and is more preferably a C / C matrix.

[0068] Before the plasma spraying, the present invention also preferably includes sandblasting the substrate. In the present invention, the pressure of the sandblasting is preferably 2-6 MPa, more preferably 4-5 MPa; the time is preferably 2-5 s, more preferably 3-4 s. The sandblasting of the substrate in the present invention can enhance the roughness of the substrate surface and strengthen the bonding strength between the substrate and the coating.

[0069] In the present invention, the spraying is preferably plasma spraying.

[0070] In the present invention, the conditions for the plasma spraying preferably include:

[0071] The current is 500-1000A; the main gas is Ar, and the main gas flow rate is 40-100SCFH; the auxiliary gas is H2, and the auxiliary gas flow rate is 5-20SCFH; the carrier gas is Ar, and the carrier gas flow rate is 3-12SCFH; the distance between the spray gun and the substrate is 70-150mm; the powder delivery amount is 10-20r / min; the power is 30-60kW; further preferred is: the current is 500-700A; the main gas flow rate is 40-90SCFH; the auxiliary gas flow rate is 5-15SCFH; the carrier gas flow rate is 4-10SCFH; the distance between the spray gun and the substrate is 90-120mm; the powder delivery amount is 15-20r / min; the power is 40-50kW.

[0072] In the present invention, the thickness of the high entropy boride coating is preferably 100 to 400 μm, and more preferably 150 to 300 μm.

[0073] The physical phase of the high entropy boride coating provided by the present invention still maintains the diffraction peak of the boride. During the spraying process, the high entropy boride undergoes a partial oxidation reaction due to the high temperature. The high entropy boride coating has high phase stability; the thickness is uniform, the coating is evenly sprayed on the surface of the substrate, and the bonding force with the substrate is strong.

[0074] In order to further illustrate the present invention, a method for preparing a high entropy boride coating provided by the present invention is described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0075] Example 1

[0076] The chemical composition of the high entropy boride in this embodiment is (Hf 0.2Zr 0.2 Nb 0.2 Ta 0.2 Sc 0.2 )B2;

[0077] According to the chemical composition of high entropy boride, the required HfO2, ZrO2, Nb2O5, Ta2O5, Sc2O3 and B4C are mixed and placed in a ball mill, and anhydrous ethanol and grinding balls are added, wherein the mass ratio of the mixture, anhydrous ethanol and grinding balls is 1:2:4, and the grinding balls are zirconia balls with a diameter of 10 mm, zirconia balls with a diameter of 8 mm, zirconia balls with a diameter of 5 mm and zirconia balls with a diameter of 2 mm with a mass ratio of 1:2:3:4; ball milling is performed at a rotation speed of 350 rpm for 5 hours; the ball-milled slurry is heated to 70°C in a water bath, and rotary evaporated at a rotation speed of 35 rpm; the wet powder obtained after rotary evaporation is dried at 100°C for 12 hours;

[0078] Graphite paper is laid in a graphite crucible, and the obtained mixture is placed on the graphite paper; the dried powder is placed on the graphite paper, and the graphite crucible is placed in a graphite vacuum furnace for sintering, and the temperature is increased to 1000°C at a heating rate of 10°C / min, and then increased to 1850°C at a heating rate of 5°C / min, and kept at this temperature for 3 hours. After sintering, the mixture is cooled to room temperature with the furnace;

[0079] The cooled powder, anhydrous ethanol and grinding balls are placed in a ball mill for ball milling, wherein the mass ratio of the cooled powder, anhydrous ethanol and grinding balls is 1:2:4, and the grinding balls are zirconia balls with a diameter of 10 mm, zirconia balls with a diameter of 8 mm, zirconia balls with a diameter of 5 mm and zirconia balls with a diameter of 2 mm in a mass ratio of 1:2:3:4, and the ball milling is carried out at 400 rpm for 6 hours;

[0080] The ball-milled slurry was sieved with a 625-mesh sieve, the sieved slurry was heated to 70° C. in a water bath, and rotary evaporated at a rotation speed of 35 rpm; the wet powder obtained after rotary evaporation was dried at 100° C. for 12 h to obtain a high entropy boride;

[0081] Put high entropy boride, deionized water and polyvinyl alcohol into a ball mill for mixing and ball milling to obtain a slurry; wherein the mass ratio of high entropy boride to deionized water is 4:6, the mass ratio of polyvinyl alcohol to high entropy boride is 0.4:100, zirconia balls are selected as grinding balls, and zirconia balls with a diameter of 10 mm, zirconia balls with a diameter of 5 mm and zirconia balls with a diameter of 2 mm are added in a mass ratio of 2:2:1, the ball-to-material ratio is 4:1, and the ball milling is carried out at a rotation speed of 250 rpm for 3 hours;

[0082] The obtained slurry is sent to a spray granulator for spray granulation to obtain spherical materials; the conditions of the spray granulation include: inlet temperature of 250°C, outlet temperature of 150°C, nozzle speed of 40r / s, and peristaltic pump speed of 40r / min;

[0083] The obtained spherical material is placed in a graphite crucible, and placed in a high-temperature furnace, and heated to 550°C at a heating rate of 2°C / min under normal pressure and vacuum conditions, and then heated to 1400°C at a heating rate of 5°C / min and kept at this temperature for 2 hours; after cooling to 30°C at a cooling rate of 5°C / min, the material is sieved with a standard sieve with an aperture of 45 to 90 μm to obtain high entropy boride microspheres;

[0084] The C / C substrate was sandblasted with a pressure of 4 MPa and a sandblasting time of 3 s. A high entropy boride coating with a thickness of 200 μm was prepared on the surface of the sandblasted C / C substrate using high entropy boride microspheres as a coating by plasma spraying. The conditions of plasma spraying were as follows: current of 580 A; main gas of Ar with a main gas flow rate of 45 SCFH; auxiliary gas of H2 with an auxiliary gas flow rate of 5 SCFH; carrier gas of Ar with a carrier gas flow rate of 4 SCFH; the distance between the spray gun and the substrate of 110 mm; powder feeding rate of 17 r / min; and power of 44 kW.

[0085] Example 2

[0086] A high entropy boride coating was prepared in the manner of Example 1, except that the temperature of the second sintering was 1600°C.

[0087] Example 3

[0088] A high entropy boride coating was prepared in the manner of Example 1, except that the temperature of the second sintering was 1800°C.

[0089] Performance Testing

[0090] Test Example 1

[0091] (1) The high entropy boride microspheres prepared in Example 1 were subjected to XRD detection to obtain an XRD spectrum, such as Figure 1 As shown;

[0092] Depend on Figure 1 It can be seen that the diffraction peaks of high entropy boride are in good agreement with TaB2 standard card PDF#38-1462, and no other impurity peaks appear. Granulation and sintering do not change the structure of the high entropy boride phase.

[0093] (2) The high entropy boride microspheres prepared in Example 1 were observed by scanning electron microscopy (SEM), and the SEM images were as follows: Figure 2 As shown, Figure 2a is a SEM image with a magnification of 400 times. Figure 2 b is a SEM image with a magnification of 1500 times;

[0094] Depend on Figure 2 It can be seen that the high entropy boride microspheres provided by the present invention have good sphericity, no obvious cracks on the surface, almost no breakage of the spherical powder, and good cohesive strength. The powder particle size is between 45 and 90 μm, and the particle size distribution is relatively uniform.

[0095] (3) The high entropy boride coating obtained in Example 1 was subjected to an X-ray diffraction (XRD) test, and the obtained XRD spectrum was as follows: Figure 3 shown.

[0096] Depend on Figure 3 It can be seen that the coating obtained in Example 1 still contains single boride and some ZrO2 peaks appear, which proves that the high entropy boride has a certain phase stability and the high entropy boride coating is successfully prepared.

[0097] (4) The high entropy boride coating obtained in Example 1 was observed by scanning electron microscopy (SEM), and the obtained SEM image is as follows: Figure 4 As shown, Figure 4 c is the SEM image of the coating surface. Figure 4 d is the SEM image of the coating cross section;

[0098] from Figure 4 It can be seen that there are molten parts and non-molten parts on the surface of the high entropy boride coating provided by the present invention. The non-molten part in the coating is formed when some particles float in the edge area of ​​the plasma jet field during the spraying process and are not fully heated or the molten droplets splash when they hit the deposited coating at high speed. The splashed molten droplets cool and solidify and are deposited on the coating surface again under the action of the jet and gravity; the molten part is deposited by normal heating. It can be seen from the SEM image of the cross section that the thickness of the coating is about 200μm, the bonding performance between the coating and the substrate is good, and the uneven morphology of the substrate surface helps to improve the bonding strength of the coating. At the same time, it can be seen that the high entropy boride coating obtained by the present invention has a high density.

[0099] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high entropy boride coating, characterized in that: The following steps are involved: The high entropy boride, dispersant and binder are mixed, and the obtained slurry is spray granulated to obtain a spherical material; The spherical material is subjected to a first sintering and a second sintering in sequence to obtain high entropy boride microspheres; the temperature of the first sintering is 500-600°C, and the holding time is 2.8-3.2 hours; the heating rate of heating to the first sintering temperature is 1-3°C / min; the temperature of the second sintering is 1400-1800°C, and the holding time is 1.8-2.2 hours; the heating rate of heating to the second sintering temperature is 3-7°C / min; The high entropy boride microspheres are used as coating and sprayed on a substrate to obtain the high entropy boride coating.

2. The preparation method according to claim 1, characterized in that: The metal elements in the high entropy boride include at least five of Hf, Zr, Nb, Ta, Sc, Ti, Lu, Tm, Er, Ho and Dy; The molar amounts of the metal elements in the high entropy borides are the same; The molar ratio of the total molar amount of the metal elements to the boron element is 1:

2.

3. The preparation method according to claim 1, characterized in that: The dispersant includes deionized water; and the binder includes polyvinyl alcohol.

4. The preparation method according to claim 1, characterized in that: The solid content of the slurry is 40wt%; The mass of the binder is 0.4 wt % of the mass of the high entropy boride.

5. The preparation method according to claim 1, characterized in that: The mixing method is ball milling; the grinding balls used in the ball milling include first grinding balls, second grinding balls and third grinding balls; The diameter of the first grinding ball is 10 mm, the diameter of the second grinding ball is 5 mm, and the diameter of the third grinding ball is 2 mm; The mass ratio of the first grinding ball, the second grinding ball and the third grinding ball is 1.8-2.2:1.8-2.2:1; The ball-to-material ratio of the ball milling mixture is 4:0.8-1.2; The ball milling mixing has a rotation speed of 200 to 400 rpm and a time of 2 to 4 hours.

6. The preparation method according to claim 1, characterized in that: The conditions of the spray granulation include: an inlet temperature of 240-280° C., an outlet temperature of 140-160° C., a peristaltic pump speed of 30-50 r / min, and a nozzle speed of 30-50 r / s.

7. The preparation method according to claim 1, characterized in that: The spraying is plasma spraying.

8. The preparation method according to claim 1, characterized in that: The thickness of the high entropy boride coating is 100-400 μm.